Driving economic sustainability in China: the role of renewable energy, green finance, and government intervention - Liang, Caiqing; Peng, Bo; Wu, Zijing (Frontiers in Environmental Science, 2026)
China is committed to achieving carbon neutrality by 2060, highlighting the importance of identifying key factors that promote sustainable economic development. Based on endogenous growth and energy-growth nexus theories, this study investigates how renewable energy, green technology innovation, green finance and government intervention affect Green Total Factor Productivity (GTFP) in 30 Chinese provinces from 2010 to 2022. To obtain robust and reliable estimation results, this study employs Generalized Least Squares (GLS), Driscoll-Kraay standard errors (D-K), and the two-step systematic Generalized Method of Moments (GMM) method for empirical analysis. The findings demonstrate that renewable energy, green finance, and green technology innovation significantly improve GTFP, with coefficients of 0.054, 2.153, and 0.091, respectively, all statistically significant at the 1% level. Notably, the impact of green finance on GTFP indicates significant geographical disparities, with the central region having the strongest effect (coefficient = 1.258). Further, the analysis indicates that GOV and GTFP have a U-shaped relationship. Moreover, the moderation effect of green finance and government intervention with green technology innovation is found to exert a positive and significant effect on GTFP, with interaction coefficients of 0.089 and 0.046, respectively.